Co-creating an inclusive science, technology, engineering, and mathematics program: a gender-responsive approach - Nurfarahin Nasri; Nurfaradilla Mohamad Nasri; Sharida Abu Talib; Nur Atiqah Jalaludin (Intelektual Pustaka Media Utama, 2026)
Gender parity in education has improved in many countries alongside global and local efforts to promote gender equity. However, in Malaysia, male participation in related fields, especially science, technology, engineering, and mathematics (STEM), is increasingly at risk due to a subtle trend of a reversed gender parity index. This qualitative research aims to examine what makes up an inclusive STEM program, with specific foci on curriculum co-creation and gender responsiveness. Through purposive sampling of various stakeholders (n=47), several rounds of focus group discussions and interviews were conducted. Thematic analysis revealed key components of an inclusive STEM program, and strategies for promoting gender-responsiveness when co-creating this program. Moreover, these findings highlight the importance of enhancing students’ engagement in STEM through participatory decision-making and tailored interventions. The research contributes to both theory and practice by making recommendations for developing more inclusive, gender-responsive learning environments in STEM education.